Scholarly Knowledge Investigation in Graduate Competency Standards Policy: Analysis of Kma 347 in 2022 - Hikmah Maulani; Jaja Jahari; Supiana (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2026)
This study aims to examine the representation of scholarly knowledge in the madrasah Graduate Competency Standards (SKL) policy as stated in the Decree of the Minister of Religion (KMA) Number 347 of 2022. Scholarly knowledge is understood as knowledge that comes from the integration of revelation (naqli) and reason (‘aqli), and is developed through a scientific, reflective, and contextual approach. This study uses a qualitative approach with a document analysis method. The main data source is the official document KMA 347 of 2022 and its attachments, supported by theoretical literature on Islamic epistemology, contemporary learning theory, and religious moderation. Data analysis was carried out using content and thematic analysis techniques to identify the scientific structure contained in the madrasah SKL. The results of the study show that the madrasah SKL contains three main dimensions of scholarly knowledge: (1) the scientific-academic dimension, which includes the ability to think critically in understanding interpretation, hadith, and fiqh; (2) the socio-affective dimension, which emphasizes religious moderation, tolerance, and social ethics as a form of Islamic sociological literacy; and (3) the religious-practice dimension, which integrates a deep understanding of worship and spiritual values. SKL is also designed based on modern learning theories such as Bloom's taxonomy, constructivism, and the scientific approach. The emphasis on contextual interpretation theory, the history of moderate Islamic thought, and the cross-school fiqh approach shows that religious moderation in SKL is not only a moral value, but also an academic domain that can be transformed in learning. This study recommends strengthening the epistemological dimension in the development of future madrasah curricula.